(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2022)
The objective of this paper is to describe the semantic strategies, or cognitive representations, that El Mercurio and La Cuarta, Chilean newspapers, create about mapuche culture, in relation to the press coverage given to the hunger strike organised by prisoners of this ethnic group. For this, the discursive strategies used by the newspapers mentioned before, and the representation of their interrelationship with the macrostructures in journalism, which finally aim to analyze the lexicalization in the configuration of the mapuche otherness, were studied. The methodology consists of Critical Discourse Analysis (CDA) –in relation to the ideological square (Van Dijk, 1999) and lexicalization– and the Velazquez’ model (2011) for the study of the journalist discourse related to the superstructure and macrostructure of news. As a conclusion, the newspapers analysed use semantic and cognitive strategies to discriminate based on ethnocentrism, giving it a specific ideological square and polarisation between Others and Us.